(untitled) (Singaporean Journal of Business Economics and Management, 2013)
Almost twenty years after democracy we find growing economic activity in the informal sector. The spaza market in Khayelitsha’ can be seen as an example of entrepreneurial activity offering an entry point to many that are excluded from mainstream economic activities. This study included 352 participants and is comprised of South African (locals) and Somali (foreigners) owned spaza shop entrepreneurs operating in Khayelitsha. In recent years foreigners have become a dominant force in this market often resulting in the closure of many local businesses. This has often given rise to xenophobic violence resulting in deaths of innocent persons. We focus on the role of culture on business practices and entrepreneurial orientation on business performance. Entrepreneurial orientation is used as a psychological concept to reflect on the level of entrepreneurial potential within the informal sector. Business practices include rudimentary financial management practices that provide a measure of financial stability of the business.